0671 Combination Of Transoral Robotic Surgery And Oropharyngeal Myofunctional Therapeutic Training For Patients With Obstructive Sleep Apnea. (27th May 2020) - Lai, Y J; Hung, C H; Lin, C Y
Abstract: Introduction: Obstructive Sleep Apnea (OSA) is a type of sleep disorder characterized by intermittent, partial or complete upper airway collapse. Mostly, moderate to severe OSA cases were recommended to treat with continuous positive airway pressure, however, some of them were withdrawn. Transoral robotic surgery (TORS) was considered for OSA patient with tongue base hypertrophy, but the success rate was only 66.9% and the symptoms might relapse because of aging and gaining weights. Myofunctional therapeutic training (MFTT) was also an alternative treatment for patients with mild to moderate OSA. In our study, we investigated the effect of TORS surgery and oropharyngeal MFTT for OSA patients. Methods: Seven adult patients were recruited, who were newly diagnosed with moderate to severe OSA (Apnea-hypopnea Index, AHI, 49.8±27.7/h). Polysomnography, questionnaire (Pittsburgh sleep quality index, PSQI; Snore Outcomes Survey, SOS), and the muscle strengths over tongue and jaw-opening were assessed before TORS surgery, 6-week and 18-week after surgery. The components of MFTT program involved jaw opening, tongue protrusion, tongue left, tongue right, tongue up and tongue down. It began at 6 th week after surgery and these patients underwent 12 weeks of the home-based oropharyngeal MFTT. During the training intervention period, subjects were interviewed every week for adjusting the treatment intensity. Results: Mean age was 45.9 years old (SD 9.8) and body mass index (BMI) was 26.6 (SD 3.6). After combination treatment of TORS surgery and MFTT, AHI-supine was significantly decreased from 66.3/h to 26.8/h (p<0.05). PSQI and SOS scores were significantly improved (-2.1, 28.8, respectively). Compared with different components of MFTT program, muscle strength of tongue protrusion was the only significant predictor of AHI-supine reduction. Conclusion: Our study presented that combination of TORS surgery and oropharyngeal MFTT could improve OSA severity and symptoms. Support: This work was supported by National Cheng-Kung University Hospital (grant number NCKUH-10802018).